Moderating Role of Legal Framework on Transformational Leadership in Implementation of Digital Literacy Program in Kenya (Global Journal of Management and Business Research, 2020)
The general objective of this study was to analyze the role of transformational leadership on the implementation of a national government multi-agency projectprogram in Kenya. The specific objectiveswereto examine the role of idealized influence andinspirational motivationand themoderating role of the legal framework on the implementation of digital literacy programs in Kenya. A descriptive and explorative research design was adopted as well asa positivism research philosophy.
Keywords: literacy; idealized influence; inspirational motivation; legal framework